Phytochemical Content and Protective Effect of Kleinhovia hospital Leaves Extract on Pancreatic Cytotoxicity in Hyperglycemic Rats - Yuliana, Yuliana; Herawati, Sianny (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Diabetes mellitus is a wide problem nowadays. Many traditional plants are used to overcome thecomplication of this disease. One of them is paliasa (Kleinhovia hospital Linn) leaves. This study aimswere to investigate phytochemical contents and the protective effects of paliasa leaves extract on pancreaticcytotoxicitybased on microscopic lesion such as hemorrhagic score and necrotic appearances, in alloxaninducedhyperglycemic rats. Male Wistar rats (three months old) were divided into four groups consistedofseven rats each. Group I was diabetic control, Group II was diabetic groups, paliasa extract (300mg/kgBW) were given by sonde for a period of 14 days prior to alloxan injection (150 mg/kg intraperitoneal).Group III was diabetic rats given 600 mg/kg BW paliasa extract and group IV was diabetic rats given 900mg for 14 days. At the end of the study, rats were sacrificed. Tissue sample ofpancreaswas then processedfor slide preparation and was stain with hematoxylin eosin.Pancreas hemorrhagic score was divided intofour criteria, focal(score 1), multifocal (score 2), extensive (score 3), and difuse (most severe, score 4).Microscopic examination was done using binocular microscope, at Laboratory ofVeterinaryPathology,Disease Investigation Centre Denpasar, Bali. Data werethenanalyzed by using analysis ofvarians. Study showed that paliasa extract could lower hemorrhagic score on pancreas of diabetic rats,even though it was not significant compared to control group (p 0,205). Phytochemical analysis showedthat paliasa leaves extract contained alkaloid, terpenoid, and flavonoid. Necrotic appearances were variedfrom pycnosis, karyorheksis, karyolysis, and vacuolization. In conclusion, paliasa leave extract may haveprotective effect on pancreas cytotoxicity.
Keywords: alloxan, paliasa extract, diabetes, phytochemical, rats